Of civil and social contracts: Azoulay after Hobbes. (1st December 2014) - Fardy, Jonathan
Ariella Azoulay's concept of 'the civil contract of photography' innovatively responds to the long tradition of social contract theory inaugurated by Thomas Hobbes. I argue that a comparative analysis between Hobbes and Azoulay (through a Schmittian lens) exposes both Azoulay's debt to 'the monster of Malmesbury', while simultaneously exposing to view the profound limits this debt imposes on Azoulay's ethical project to wrest the concept of citizenship free from the ideology of the nation state.